2019 IEEE International Conference on Big Data (Big Data) 2019
DOI: 10.1109/bigdata47090.2019.9006245
|View full text |Cite
|
Sign up to set email alerts
|

Context-Augmented Software Development in Traditional and Big Data Projects: Literature Review and Preliminary Framework

Abstract: Software development is a complex activity which depends on diverse technologies and people's expertise. The approaches to developing software highly depend on these different characteristics, which are the context developers are subject to. This context contains massive knowledge, and not capturing it means knowledge is continuously lost. Although extensively researched, context in software development is still not explicit, nor proposed into a broader view of the context needed by software developers and too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The proposed paradigm is one step further towards bringing more knowledge to developers, both experienced and novice, during specific software development activities. This paradigm builds upon our previous work on reusing relevant information to support developers in executing their tasks [19] and the relevance of context in software development projects [20].…”
Section: The Expected Futurementioning
confidence: 99%
“…The proposed paradigm is one step further towards bringing more knowledge to developers, both experienced and novice, during specific software development activities. This paradigm builds upon our previous work on reusing relevant information to support developers in executing their tasks [19] and the relevance of context in software development projects [20].…”
Section: The Expected Futurementioning
confidence: 99%
“…Therefore, some studies might have worked with the context in SE but without explicitly defining context nor having its usage motivated [6]. Nonetheless, several studies have considered the context in software development and identified it as "context" [7].…”
Section: A Context In Software Developmentmentioning
confidence: 99%
“…Consider the example illustrated in [7], where Gabi is a software developer who has been programming in Java for nine years and has recently been working on project X. When there is a new project, one of Gabis goals is to create a minimal viable product (MVP) to show her clients.…”
Section: Chatbots and Rasamentioning
confidence: 99%
“…Although GitHub users also work collaboratively, we can nonetheless clearly identify individual productivity as all code "commits," "issues," and "pull requests" are directly attributed to the person who published them. Third, the sheer amount of available data allows us to collect sufficient information on both male and female developers and to take general time trends into account (Melo et al 2019). These advantages outweigh some of the obvious limitations that GitHub data havenamely, the limited individual-level information that can be retrieved about the developers (most importantly, we lack information about developers' parental status) and the high selectivity of this population, which limits the conclusions we can draw for the general population.…”
mentioning
confidence: 99%